Ecogeographical Analysis of Hakea (Proteaceae) in South-western Australia, with Special Reference to Leaf Morphology and Life Form. - Groom, Philip; Lamont, Byron (1996)
The genus Hakea Schrader (Proteaceae) has its world centre of diversity in south-western Australia; the majority (c. 70%) of species are endemic to this region. To examine the distribution of Hakea within south-western Australia, canonical correspondence analysis (CCA) was used on species presence and bioclimatic parameters in 0.5 deg x 0.5 deg latitude-longitude grid cells. Of the 12 bioclimatic attributes initially applied, annual temperature and rainfall data, and indices of their variation, were best related to species distribution. Clustering of the species (on the CCA ordination) produced five distinct groups (not including species near the origin of the ordination) roughly representing floristic regions of south-western Australia (Avon, Irwin, Eyre-Roe, southern Darling, northern-central Darling). Species distribution was then related to four morphological groups based on their leaf type (broad, terete) and post-fire life form (non-sprouter, resprouter). The highest percentage of terete-leaved non-sprouters occurred in areas of low-moderate rainfall and large annual temperature ranges (Avon and Eyre-Roe clusters), whereas terete-leaved resprouters displayed a very patchy distribution, accounting for less than 20% of the hakeas present in most of the grid cells. Broad-leaved resprouters dominated areas of strongly seasonal rainfall (Irwin and northern-central Darling clusters), with few species occurring in the drier Avon and Eyre-Roe districts. Broad-leaved non-sprouters were best represented in areas of low annual temperature (southern Darling and Eyre-Roe clusters). The distribution of non-sprouters and resprouters may be due to climatic factors affecting seedling recruitment and/or fire frequencies. Leaf morphology appears to be more directly related to species distribution, as broad leaves are favoured in regions of medium-high, seasonal rainfall (less stressful habitats) while terete leaves are better adapted to tolerate hot, dry environments.